Effect Of Malaysian Thermal Spring Water As Adjunct Therapy For Mild To Moderate Acne Vulgarisms - A Prospective Randomised, Controlled Split Face Study - Ummu Aiman Faisal; Adawiyah Jamil; Hafiz Jaafar; Wan Syaidatul Aqma; Mohan Arumugam (The Medical Journal of Malaysia, 2024)
Indexed by MyCite